Sullivan, Phyllis. 3. Part three of interview about Pouch Cove. - Chun Lau, Po
Phyllis Sullivan is joined by Eilieen Baldwin at her home, where they discuss dances, nicknames, fishing, women's work, and community change. 00:00 – heating water on stove for dishes and laundry; 0:51 – Mr. Easterbrook mailman; Mr. Gruchy; location of first post office; 2:04 – Po moving to Pouch Cove; 2:37 – people moving into Pouch Cove; back road becoming filled with houses; Allan Hudson’s house on courting lane; 3:48 – SUF Hall dances; first dance with Billy Bubbler; 4:40 – Phyllis’s first dances; 5:14 – live music; accordion; David Bragg and Charlie Strugnell playing accordion; David Locke; 6:02 – fisherman’s soup supper and concert; Frank Strugnell dancing; 6:48 – nicknames; Frank Sullivan’s nickname; 8:48 – father and Jake Langmead fishing together; sharing boat and catch; Alex Gruchy buying fish; going to Gruchy’s store at recess; 9:56 – doing homework by kerosene lamp; 10:30 – women spreading fish on flakes; 11:30 – children helping move fish piles; covering fish; drying; 13:01 – women salting fish; 13:30 – flakes along shore; structures; 14:15 – hungry month of March; food scarcity after winter; bulk food for winter; salt meat; 15:23 – father going seal hunting; 16:47 – Shirley Bragg’s house; 17:03 – women working hard; bringing up barge; splitting fish; 17:46 – husband buying boat built by Andrew Sullivan; went fishing with Henry Sullivan; working as carpenter; 18:30 – NL light and power; 18:50 – tearing down old school; developing land; 21:27 – discussing grandchildren.